Direct observation of preferential occupation of zinc ions in (Fe1-xZnx)2Mo3O8. (1st March 2022) - Ji, Y.; Ding, Y.F.; Wang, W.P.; Wang, H.X.; Yang, J.K.; Shen, X.; Yao, Y.; Yu, R.C.
Abstract: The occupation of Zn ion in (Fe1-x Znx )2 Mo3 O8 was investigated by many experimental analysis methods and theoretical calculations, but the corresponding direct observation has not yet been reported so far. In this work, it is confirmed that the Zn ion prefers to occupy the tetrahedron position in the FeZnMo3 O8 by using scanning transmission electron microscopy. Besides, the (Fe0·75 Zn0.25 )2 Mo3 O8 shows ferrimagnetism by doping Zn ions, and the valence of Fe ions remains +2 indicated by the X-ray photoelectron spectroscopy results. Highlights: Direct experimental evidence for the occupation of Zn ions in the tetrahedron sites in FeZnMo3 O8 is displayed. The valence state of Fe ions in Fe2 Mo3 O8  and (Fe0.75 Zn0.25 )2 Mo3 O8  is indicated.